Transport-related social exclusion and mobility in developing countries: the South African case - Luke, Rose (Frontiers in Sustainable Cities, 2024)
Introduction Transport-related social exclusion has been studied in many countries, and from many different perspectives. In Africa, however, there is little recent research into the phenomenon, even though African cities tend to have poor transport services, urban sprawl is extensive usually resulting in long travel times and high travel costs, and certain areas experience high levels of crime. By implication, there are several factors that impact the ability of people to access economic and societal opportunities, however these are not well documented. Building on previous work from several authors, this research sought to describe transport-related social exclusion in a large metropolitan area in an emerging economy. Methods Using a qualitative methodology, 60 interviews were conducted with City of Johannesburg residents. The data was analyzed using manual thematic and classic content analysis. Results The study found that residents often did not have access to services due to availability, but also that economic, geographic and fear-based exclusion were particularly prevalent in the sample, although there were several other psychological exclusion dimensions, as well as information exclusion. Discussion This study is the first recent study in South Africa to consider a wide range of commuters from varying demographic strata, thus providing a novel perspective on TRSE in a major urban area in the country. The study recommends that policy actions be considered, taking into account the minibus taxi industry, which is often overlooked in government policy. TRSE should also be an inherent element in urban (and other) transport planning, as well as take into account the broader societal realities faced by citizens. Future research directions include conducting broader quantitative studies across a variety of urban areas in South Africa, and beyond, to determine specific TRSE dimensions in various urban areas. Policy analysis is also recommended, to determine TRSE policy gaps and align interventions with specific commuter needs.